The Effect of Marketing Mix on Purchase Decisions at Éclair Coffee in Mataram City - Wijaya, Levina Apriyeni; Nurlaela, Luthfiyah; Yushila, Aulia Bayu; Nurfatimah, Ratna Palupi (Universitas Negeri Padang, 2025)
The take a look at ambitions for look at how application of a advertising blend method concerning 4 key additives, namely product, rate, distribution, and advertising, contributes to consumer purchasing choices at Éclair coffee in Mataram town. the idea for this have a look at stems from the fast growth of the culinary industry and increasingly competitive espresso stores, which necessitates appropriate advertising strategies to influence client interest and selections. The studies technique used a quantitative method with an associative design, at the same time as data collection become accomplished through the distribution of Google paperwork-based questionnaires to a hundred respondents the usage of purposive sampling as a part of a non-probability sampling approach. The consequences discovered that the product and merchandising factors had a sizeable impact on buying selections, even as the fee and vicinity (distribution) variables did now not show a vast person affect. however, when tested together, the four advertising and marketing mix variables performed a role in purchasing choices with an standard contribution of 39.1%, so it may be concluded that product and merchandising are the principle elements that decide consumer choices. based on these findings, Éclair coffee desires to prioritize improving product quality and strengthening extra creative promotional initiatives. similarly, it's also vital to reevaluate pricing and region choice policies to stay applicable, aggressive, and capable of aligning enterprise approach with evolving customer dynamics and tendencies.